Projeto de um detector de pontos-chave em arritmias cardíacas para auxílio em sistemas de cardioversão - Aparecido, Richard de Oliveira (2018)
The purpose of this work is to develop a process capable of identifying the appropriate points in cardiac arrhythmias for cardioversion, relying on the modified Pan and Tompkins methodology. Having recourse to this methodology, the R peaks of the QRS complex and the T waves were found; using these characteristics found along with decision blocks, the simulator satisfyingly recognized Ventricular Tachycardia in electrocardiographic signals (ECG) taken from arrhythmia databases (MIT-BIH's Arrhythmia Bank, MIT-BIH's Malignant Ventricular Fibrillation Bank and Creighton University's Bank). The use of decision blocks and the identification of sustained ventricular tachycardia by the designed algorithm, served as the basis for recognition of reasonable points where the cardioversion procedure could occur.